Are the effects of informational interventions driven by salience? - Eric Bettinger; Nina Menezes Cunha; Guilherme Lichand; Ricardo Madeira (University of Zurich, Department of Economics, 2020)
Informational interventions have been shown to significantly change behavior across a variety of settings. Is that because they lead subjects to merely update beliefs in the right direction? Or, alternatively, is it to a large extent because they increase the salience of the decision they target, affecting behavior even in the absence of inputs for belief updating? We study this question in the context of an informational intervention with school parents in Brazil. We randomly assign parents to either an information group, who receives text messages with weekly data on their child's attendance and school effort, or a salience group, who receives messages that try to redirect their attention without child-specific information. While information has large impacts on attendance, test scores and grade promotion relative to the control group, outcomes in the salience group improve by at least as much, and to a greater extent among students with lower attendance at baseline. Our results suggest that alternative interventions that manipulate attention can generate larger impacts at lower costs, and have implications for the design of informational interventions across a range of domains.
Keywords: C93; D83; D91; I25; I31; 330; Information; Salience; Inattention